HIGH MYELOPEROXIDASE LEVEL AS A PROGNOSTIC FACTOR CARDIOVASCULAR EVENTS AT SIX MONTH IN PATIENTS PRESENTING WITH ACUTE CORONARY SYNDROME - Budiana, I Putu Gede; Wita, I Wayan; Widiana, I Gede Raka (Medicina, 2015)
Cardiovascular disease (CVD) is the highest leading cause of death worlwide. Inflammation has beenimplicated  in  all  stages  in  the  evolution  of  atherosclerotic  plaques. Myeloperoxidase  (MPO)  is  anenzyme linked to both inflammation and oxidative stress. The aim of this study was to assess wetherhigh level of MPO is a prognostic factor of cardiovascular events at six month in patients presentingwith acute coronary syndrome (ACS). This study was a prospective cohort study, which took place atSanglah General Hospital Denpasar from 10 December 2011 until 10 December 2012. Subjects of thisstudy were 60 ACS patients which were enrolled by consecutive sampling. MPO levels was measuredat the first admission and the cardiovascular events during six month were observed. Sixty sampleswere involved in this study, 9 unstable patients  (11%), 11  NSTEMI patients (18.3%), and 40 STEMIpatients (66.7%). In 6 months observation, there was 14 (23.3%) patients had cardiovascular events.Nine patients (15%) had high MPO levels and 51 patients (85%) had low MPO levels.  The result of thisstudy were the ACS patients with high levels of MPO were tend to have more adverse cardiac events [hazard ratio (HR) 1.4; 95 % confidence interval (CI) 0.39 to 5.22; P = 0.591]. The relationship betweenMPO levels and incident cardiovascular event according to ARR (absolute risk reduction) was 11.76 %and NNT  (number need  to  treat) was 8. High MPO  levels gives benefit of  long  term prognostic  inpatients with acute coronary syndrome.  [MEDICINA 2015;46:16-21]. Penyakit  kardiovaskular merupakan  penyebab  kematian  tertinggi  di  seluruh  dunia.  Inflamasimemegang peranan pada stadium pembentukan plak aterosklerosis. Myeloperoxidase (MPO) adalahenzim yang berhubungan dengan inflamasi dan stres oksidative. Tujuan penelitian ini adalah untukmengetahui kadar MPO yang tinggi sebagai faktor prognostik kejadian kardiovaskular dalam 6 bulanpada  penderita  sindrom  koroner  akut  (SKA). Penelitian  ini merupakan  kohort  prospektif,  yangbertempat di RSUP Sanglah dari 10 Desember 2011 sampai 10 Desember 2012. Sampel penelitianadalah 60 orang yang diambil secara consecutive sampling. Sampel yang memenuhi kriteria inklusidiperiksa kadar MPO saat masuk rumah sakit dan diamati kejadian kardiovaskular (KKV) selama 6bulan. Enam puluh penderita SKA yang dilibatkan dalam penelitian ini terdiri dari 9 orang pasienAPTS (15 %), 11 orang pasien NSTEMI (18,3 %) dan 40 orang pasien STEMI (66,7 %). Dalam pengamatanselama 6 bulan, didapatkan sebanyak 14 (23,3 %) orang pasien yang mengalami KKV. Sebanyak 9orang (15%) dengan kadar MPO tinggi dan 51 orang (85%) dengan MPO rendah. Pada penelitian inididapatkan  bahwa  pasien SKA  dengan kadar MPO  tinggi memberikan  outcome  yang  lebih  tinggidibanding dengan kadar MPO yang rendah (HR 1,4; IK 95 % 0,39-5,22; P = 0,591). Besar efek dari MPOterhadap KKV yang diukur dengan ARR (absolute risk reduction) adalah 11,76 % dan NNT (numberneed to treat) sebesar 8. Kadar MPO yang tinggi memberikan manfaat dalam prognostik jangka panjangpada pasien SKA. [MEDICINA 2015;46:16-21].
Keywords: acute oronary syndrome, MPO